Examples of good experiences for child-friendly cities. Comparison of sustainable practices in Italy and around the world - D'Amico, Annunziata (TeMA - Journal of Land Use, Mobility and Environment, 2024)
An approach to urban planning that focuses on children is a crucial element for creating inclusive, resilient and competitive cities in which to live, work and grow. The image of a city that is increasingly inadequate to meet the needs of the youngest citizens emerges from the urban transformation that has characterized the last decades, oriented to the car, which endangers the safety and quality of the environment. The contribution aims to provide a scientific framework on recent policy, practice and academic research on the topic of child-friendly cities: are identified, from a review of national and international best practices, directions and solutions for achieving child-friendly cities that help counter socio-spatial inequalities and promote the well-being of this population group, in line with Goals 11 of the United Nations 2030 Agenda for Sustainable Development. The comparison between the different initiatives and experiments, shows that children can be powerful agents in the design and implementation of better urban environments.